The main indicators evolution from the fruits and vegetables sector - Raluca Alexandra Necula; Diana Maria Necula; Manea Drăghici; Valentina Tudor (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
Romania is a country with a high production potential for the vegetables and fruits, due in particular to the high natural fertility of soils and to the climate diversity. Besides the favorable conditions for the production of fruits and vegetables, it should be mentioned that Romania is a country which is concerned with agriculture, to meet the economic and technical requirements characteristic of the market economy. In this paper we analyze, by comparison, the areas, the average and total production, the purchase and sales price, the incomes obtained from the sale and the trade balance on the main vegetable and fruit crops, in order to determine the evolution of these indicators and to determine the situation of this agricultural sector in Romania. By using specific indicators, the trend followed by the fruit and vegetable sector can be determined, which can be used to assess the actual real situation of Romanian horticulture and to determine the next steps to improve future results.
Keywords: E29; E30; F10; 330; surfaces; production; consumption; trade; evolution